2023
DOI: 10.1186/s40560-023-00662-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical power and 30-day mortality in mechanically ventilated, critically ill patients with and without Coronavirus Disease-2019: a hospital registry study

Abstract: Background Previous studies linked a high intensity of ventilation, measured as mechanical power, to mortality in patients suffering from “classic” ARDS. By contrast, mechanically ventilated patients with a diagnosis of COVID-19 may present with intact pulmonary mechanics while undergoing mechanical ventilation for longer periods of time. We investigated whether an association between higher mechanical power and mortality is modified by a diagnosis of COVID-19. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…Most MP studies with different outcomes included patients with ARDS [20][21][22] and a strong association between MP and mortality was observed. This association has also been observed in patients without ARDS [24][25][26][27] , and recently in patients with COVID-19 23,27 . Our results in the sub-analyses of patients with COVID-19 suggest that MP maintains a close relationship with mortality, although the contribution to IMV days appears to be lower than in non-COVID-19 patients.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Most MP studies with different outcomes included patients with ARDS [20][21][22] and a strong association between MP and mortality was observed. This association has also been observed in patients without ARDS [24][25][26][27] , and recently in patients with COVID-19 23,27 . Our results in the sub-analyses of patients with COVID-19 suggest that MP maintains a close relationship with mortality, although the contribution to IMV days appears to be lower than in non-COVID-19 patients.…”
Section: Discussionsupporting
confidence: 62%
“…Given that IMV is a continuous process that can result in VILI at any point during IMV, it is logical to expect that the amount of time the lung is exposed to a MP above the safe cut-off point will result in an increased risk of VILI 37,38 . MP data from the rst hours or days of IMV and with spot measurements throughout the day should be interpreted with caution [21][22][23][24][25][26][27]36 . Similar works have been carried out by Serpa et al in 2018 24 and Zhu et al in 2021 25 with data from the MIMIC III an e-ICU database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study evaluating Vt based on ideal body weight found that even after normalization to the predicted body weight, the same Vt can generate different lung strains and different lung damage based on individual lung conditions [ 38 ]. A retrospective analysis of MP in COVID-19 (coronavirus disease 2019) and non-COVID-19 ARDS patients was performed in 1737 patients with almost 30% mortality [ 39 ]. The median MP during the first 24 h of ventilation was 19.3 [14.6–24.0] J/min in patients with and 13.2 [10.2–18.0] J/min in patients without COVID-19, and higher MP was associated with increased mortality independent of COVID-19.…”
Section: Mp As a Marker Of Outcomementioning
confidence: 99%
“…AWP and volume form a spirometry loop, providing information regarding lung mechanics. In addition, previous studies reported that mechanical power was associated with ventilator-related lung injury 17 19 . AWP and VOL both play an important role in calculating mechanical power 20 .…”
Section: Introductionmentioning
confidence: 99%